Indicators of students' satisfaction of quality education services in some selected universities in Ghana - Amoako, I.; Asamoah-Gyimah, K. (South African Journal of Higher Education, 2020)
Enhancing quality of educational services in higher education is an issue of concern for all stakeholders of education in the 21st Century. Students’ assessment of educational services are often seen as an efficient tool for improving quality of teaching and learning in tertiary schools. The aim of the study was to investigate factors that contribute to students’ satisfaction of education services as a quality assurance module for universities. A descriptive cross-sectional survey design was used for the investigation. Following a multi-stage sampling procedure, 1500 students were sampled from three public universities in Ghana. Student satisfaction (SS) and Quality assurance questionnaire (QAQ) for students were developed to measure satisfaction of students related to the educational services that they receive in their campuses. Covariance-Based structural equation modeling, specifically, Analysis of Moment Structures (AMOS) was used to validate the instrument and to test the study hypotheses. Findings of the study revealed that “instructional environment”, “technological environment” and “psychological environment” were predictors of students’ satisfaction in the context of how students see academic institution to be quality centered. The study recommended that universities in Ghana should emphasize and prioritize students’ satisfaction in their quality assurance framework as a way of sustaining quality provision of educational services.